Exploring Podcast and Teaching Writing, Why Not? - Dodi Erwin Prasetyo (Edukasi, 2022)
There were very extremely rare study exploring the integration of podcast and the writing skill. Therefore, this paper aimed at discussing pedagogical aspects toward the utilization of podcast for writing skill, at exploring the use of podcast for writing skill, at conveying some benefits and weakness toward the use of podcast for writing lesson. As conceptual paper, this study used library research method. Thus, the data were gathered via research paper, book, journal and broader relevance references. The findings were that students challenge in writing in terms of lack of grammar, lack of vocabulary acquisition and so forth, teachers challenge in terms of strategy’ usage to enhance every different students’ lack level, and ICT challenge in terms of the lack of technical support, discouragement to use it, less confident and so forth. There were five steps in integrating podcast, namely preparation, composing, recording, revising and publishing. The preparation was to set technical devices and software. The composing was to list writing materials such as its topic, objectives, writing strategy and so forth. The recording was to record all the content. Meanwhile the revising was to revise in terms of content writing material, voice clarity, visual and so forth. Then the publishing was to publish in the online platforms. The suggestions were provided for pedagogic aspect and future research.